Combined experimental and density functional theory study on the Pd-mediated cycloisomerization of o-alkynylnitrobenzenes - synthesis of isatogens and their evaluation as modulators of ROS-mediated cell death - Ramana, Chepuri V.; Patel, Pitambar; Vanka, Kumar; Miao, Benchun; Degterev, Alexei (European Journal of Organic Chemistry, 2010)
Highly selective cycloisomerization of o-alkynylnitrobenzenes, leading to isatogens, has been achieved by employment of a Pd-II complex. This reaction is very general and functional-group-tolerant. The possible mechanism of this reaction was investigated with the help of DFT calculations. Three possible pathways - namely, the addition of the nitro group either in (i) 5-exo-dig or (ii) 6-endo-dig mode and (iii) halopalladation - and subsequent intramolecular events have been considered and studied in detail. These investigations revealed that pathway (i) is the favored route to isatogen formation. A preliminary screening of the available isatogens reveals the 2-alkylisatogens to be novel ROS scavengers capable of inhibiting cellular necroptosis.
Keywords: Anthranil; cyclization; Density functional calculations; isatogens; Nitro-alkyne cycloisomerization; Palladium

InCl3-mediated addition of indole to isatogens: an expeditious synthesis of 13-deoxy-isatisine A - Kumar, Chepuri V. Suneel; Puranik, Vedavati G.; Ramana, Chepuri V. (Chemistry-A European Journal, 2012)
A strategy directed towards the total synthesis of isatisine A that involves several late-stage metal-catalyzed transformations that address the key carboncarbon and carbonheteroatom bond formations has been developed. As a part of this strategy, methods for the addition of indoles to isatogens that lead selectively to either 2,2-disubstituted N-hydroxyindolin-3-one or 2,2-disubstituted indolin-3-one compounds have been developed by employing InCl3 as a catalyst or as the reagent. The present methods provide the first examples of the additions of indoles to the isatogen nucleus. To demonstrate its viability, the synthesis of 13-deoxy-isatisine A has been completed in ten steps from a known and easily available lactone.
Keywords: indium; indoles; isatogens; Natural products; Total synthesis

Ru(II)-catalyzed C3-H functionalization of indoles with isatogens - Hegde, Chaitra Narayan; Rajeshkumar, Thayalan; Maron, Laurent; Ramana, Chepuri V. (Advanced Synthesis & Catalysis, 2026)
A simple methodology for the synthesis of the 2-(1H-indol-3-yl)indolin-3-one core present in various natural products is developed. This method comprises Ru(II)-catalyzed regioselective addition of indole to isatogen, along with N & horbar;O bond reduction. A range of indolin-3-one compounds incorporating a C2-indolyl unit are synthesized under catalytic conditions in good yields, including the natural products halichrome A and metagenediindole A. With the help of control experiments and density functional theory calculations, a plausible mechanism founded upon the involvement of a bimetallic Ru complex is proposed.
Keywords: 2-(1H-indol-3-yl)indolin-3-one; indoles; isatogens; N & horbar; O bond reduction; pseudoindoxyl natural products